Reggae y rastafari. Dos formas de entender el Caribe: Written by Juan David Chacón Benítez and César Cortez Méndez (Mayéutica Revista Científica de Humanidades y Artes, 2023)
This text is a critical review of the book Reggae y rastafari. Dos formas de entender el Caribe, written by Juan David Chacón Benítez and César Cortez Méndez. The authors reconstruct the history of Rastafari culture from the origins of the African presence in the Caribbean, analyze its impact in the region and study reggae as a musical expression, the role of record labels in its commercialization and the variants of this rhythm throughout its history.
Keywords: reggae; rastafari; Caribbean